2017
DOI: 10.1021/acs.jpca.7b09715
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Energetic Properties of Haloacetonitrile–BCl3 Complexes: Computations and Matrix-IR Spectroscopy

Abstract: The FCHCN-BCl and ClCHCN-BCl complexes were investigated by quantum-chemical computations and low-temperature, matrix-isolation-IR spectroscopy. Theory predicts two stable equilibrium structures, with distinctly different B-N distances, for both complexes. One set of structures, which correspond to the global energy minima, exhibit B-N distances of 1.610 and 1.604 Å for FCHCN-BCl and ClCHCN-BCl, respectively (via M06-2X/aug-cc-pVTZ). The corresponding binding energies are 5.3 and 6.3 kcal/mol. For the metastab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In fact, the CH 3 SiCl 3 –NH 3 and CH 3 GeCl 3 –NH 3 systems exhibit two distinct R‐axial structures with distinctly different M‐N bond distances, a phenomenon we have encountered before in our studies of nitrile‐BCl 3 complexes. [ 39,40 ] For the most part, these structures lie 2 to 3 kcal/mol above the respective R‐equatorial structures. The exceptions are the short‐bond forms of the RMCl 3 –NH 3 complexes, which lie about 4 to 6 kcal/mol above their R‐equatorial counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the CH 3 SiCl 3 –NH 3 and CH 3 GeCl 3 –NH 3 systems exhibit two distinct R‐axial structures with distinctly different M‐N bond distances, a phenomenon we have encountered before in our studies of nitrile‐BCl 3 complexes. [ 39,40 ] For the most part, these structures lie 2 to 3 kcal/mol above the respective R‐equatorial structures. The exceptions are the short‐bond forms of the RMCl 3 –NH 3 complexes, which lie about 4 to 6 kcal/mol above their R‐equatorial counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…We found that M06-2X/6-311 + G(d) meets the requirements, providing a close agreement with structural parameters; the diffuse functions were included to improve the accuracy of charge transfer interactions. [27,29,30,38] Classical (i. e. non-QMT) reaction rates were computed using canonical variational transition state theory (CVT), [39] with QMT contributions added with the small curvature tunneling (SCT) [40,41] method; a step size of 0.001 Bohr and quantized reactant state tunneling (QRST) for the reaction coordinate mode were used. [42] The M06-2X/6-311 + G(d) electronic energies were corrected with a double layer method (the interpolated single-point energy -ISPE- [43] ), where the energies of reactants, products, and transition states were recomputed at the CCSD(T)/CBS level (obtained from aug-cc-pVTZ and aug-cc-pVQZ extrapolation with β coefficients of 5 and 3 for the HF and post-HF correlation, except for Br where an aug-cc-pvTZ-PP and aug-cc-pvQZ-PP basis set was employed).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The barriers between these two minima lie between 4 to 11 kJ mol −1 with respect to the meta‐stable LB, and their corresponding reaction energies are in the range of 5–20 kJ mol −1 [29,30] . This would, in principle, make it possible to observe both geometries if a high‐temperature mixture of the two configurations is fast‐cooled to cryogenic conditions, keeping the system in the out‐of‐equilibrium original state by its kinetic barrier.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%